2018
DOI: 10.3390/math6080129
|View full text |Cite
|
Sign up to set email alerts
|

The Analytical Solution for the Black-Scholes Equation with Two Assets in the Liouville-Caputo Fractional Derivative Sense

Abstract: It is well known that the Black-Scholes model is used to establish the behavior of the option pricing in the financial market. In this paper, we propose the modified version of Black-Scholes model with two assets based on the Liouville-Caputo fractional derivative. The analytical solution of the proposed model is investigated by the Laplace transform homotopy perturbation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Hence, further investigation of such models model is an active topic of research. [13][14][15] The SVCJ model for the value of asset S t and its variance V t satisfies 1…”
Section: And the References Therein)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, further investigation of such models model is an active topic of research. [13][14][15] The SVCJ model for the value of asset S t and its variance V t satisfies 1…”
Section: And the References Therein)mentioning
confidence: 99%
“…These mathematical models and their usefulness were later discussed in Eraker et al As a matter of fact, the authors confirmed that the SVIJ and SVCJ models furnish the correct fitting, but SVCJ is more straightforward to approximate because jumps in returns and volatility are simultaneous. Hence, further investigation of such models model is an active topic of research …”
Section: Introductory Notesmentioning
confidence: 99%
“…Chen and Wang [13] presented a second-order Crank-Nicolson alternating direction implicit (ADI) scheme for solving a 2D spatial fractional BS equation. Sawangtong et al [14] proposed the BS equation with two assets based on the Liouville-Caputo fractional derivative. In [15], Zhan et al developed numerical methods for the time fractional BS equation.…”
Section: Introductionmentioning
confidence: 99%
“…Farhadi and Erjaee (2018) introduced a timefractional derivative for solving the B-S equation. Sawangtong et al (2018) investigated an analytical solution for undertaking the B-S equation with two assets using the Laplace transform HPM approach in the Liouville-Caputo fractional derivative sense. Yavuz and Ozdemir (2018) initiated a conformable fractional adomian decomposition method (CFADM) and conformable fractional modified HPM to tackle the fractional B-S equation.…”
Section: Introductionmentioning
confidence: 99%